Freestanding ultrathin bismuth-based materials for diversified photocatalytic applications. Issue 44 (29th October 2019) - Xiong, Jun; Song, Pin; Di, Jun; Li, Huaming; Liu, Zheng
Abstract : Freestanding ultrathin bismuth-based materials with suitable energy band structure have been demonstrated as outstanding photocatalysts for different applications. Abstract : The emerging ultrathin materials with a suitable energy band structure have been regarded as a new type of photocatalyst. Among them, bismuth-based ultrathin materials display intriguing photocatalytic performance due to the unique structural and electronic properties, strong light response and appealing energy band structure. This critical review summarizes recent progress in the design and tailoring of diversified Bi-based ultrathin materials for various photocatalytic applications. We start with the introduction from the crystal structure, materials design and synthesis of various Bi-based ultrathin photocatalysts, such as bismuth oxide, bismuth oxyhalides, Bi2 WO6, Bi2 MoO6, BiVO4 and so on. Then, strategies for local atomic arrangement, electronic structure, and carrier concentration tuning, so as to boost the performance, are summarized, such as crystal facet control, bismuth-enrichment strategy, surface adjustment, heteroatom doping, defect engineering, co-catalyst modification, and utilization of solid solutions, single atoms, and heterojunctions. Furthermore, advancements of versatile photocatalytic applications over Bi-based ultrathin materials are discussed, including oxygen evolution, hydrogen evolution, organic syntheses, CO2 reduction, N2 reduction, and pollutant removal, with an emphasis on the structure–activity relationship. Finally, the existing challenges and future research opportunities are also presented.